The Basic Concepts of Evaluation and Its Implementation in IRE Lessons in The Pandemic Era - Munaya Ulil Ilmi; Farid Setiawan; Maulida Nurul Hikmah; Arrum Kharisma; Dimas Feryawan; Aiman Affan Hanafie (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
This study aims to describe the nature of evaluating educational policies and their implementation in IRE subjects at SMK Negeri 3 Yogyakarta during the Covid-19 pandemic. This research is descriptive qualitative research. The results showed that evaluation must always be carried out by adjusting the situation and needs of students in order to achieve educational goals. The period of the Covid-19pandemic changed the entire order of life, including in the realm of education. Education that was originally carried out offline is now being implemented online. This has an influence on the achievement of educational goals. This change has forced education policymakers at SMK Negeri 3 Yogyakarta to evaluate Islamic Education learning by simplifying learning. This simplification is Carried out by replacing practicum activities with memorizing and chanting the Koran verse s roommates are sent via WhatsApp, Google Drive, or Telegram.